GAMBARAN PENGETAHUAN DAN SIKAP IBU TENTANG GERAKAN 1000 HARI PERTAMA KEHIDUPAN - Yessy Octa Fristika (JURNAL KESEHATAN INDRA HUSADA, 2021)
The first 1000 days of life are a period of accelerated growth and development starting from the formation of the fetus in the womb until the child is 2 years old. In that period, there is brain development, body growth, the development of the body's metabolic system and the formation of the immune system that is so fast. This research aims to see the description of knowledge and attitudes of mothers about the movement of the first 1000 days of life in RT.003 RW.003 Tanjung Powder, Kel. Bukit Baru, Kec. Ilir Barat I Palembang in 2020. This study used a descriptive design with a cross sectional approach. The analysis used is univariate. The research sample was taken by purposive sampling. The number of samples in this study amounted to 20 samples. Based on the research, the knowledge that most mothers had bad knowledge, namely 16 people (80%) and mothers who had good knowledge, namely 4 people (20%). Based on the attitude that the mother's attitude towards the movement of the first 1000 days of life has a bad attitude as many as 12 people (80%) and a good attitude of mothers as many as 8 people (40%). The results of this study recommend to the Head of RT.003 RW.003 and the community at RT.003 RW.003 to increase information about health, especially about the movement for the First 1000 Days of Life. This recommendation is also given to other researchers who intend to conduct research on the 1000 HPK movement in order to involve more samples and variables studied with different designs and use instruments that have standard validity and reliability values.